2010
DOI: 10.1097/mpg.0b013e3181aed70b
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Content of Parenteral Nutrition in Neonates: Measured Versus Calculated Levels

Abstract: Al exposure exceeded the FDA recommended maximum limit for all patient samples; however, the actual measured Al content of all the samples was significantly less than the calculated Al content based on manufacturer's labels. These findings suggest that manufacturers label their products with actual Al content at the time of product release rather than at time of expiration. Periodic monitoring of Al levels should be considered with prolonged PN therapy. Changes in manufacturing processes, including the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 18 publications
4
41
2
Order By: Relevance
“…Terms & Conditions of access and use can be found at http:// www.tandfonline.com/page/terms-and-conditions Introduction Aluminium (Al) is a ubiquitous element but its impact on biological systems has been subject of much controversy over the past decades (Campbell and Bondy 2000). Research has revealed that aluminium is toxic to humans and associated with significant central nervous system toxicity and bone and liver damage (Ganrot 1986;Nayak and Chatterjee 2000;Yokel 2000;Kumar and Gill 2009;Poole et al 2010). …”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Terms & Conditions of access and use can be found at http:// www.tandfonline.com/page/terms-and-conditions Introduction Aluminium (Al) is a ubiquitous element but its impact on biological systems has been subject of much controversy over the past decades (Campbell and Bondy 2000). Research has revealed that aluminium is toxic to humans and associated with significant central nervous system toxicity and bone and liver damage (Ganrot 1986;Nayak and Chatterjee 2000;Yokel 2000;Kumar and Gill 2009;Poole et al 2010). …”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Although there has been a decline in the rates of aluminum accumulation in populations at risk, such as those with renal insufficiency, those on chronic total parenteral nutrition (TPN), and chronic antacid users, these patient populations are still at risk for aluminum toxicity [597,598]. Aluminum contamination of parenteral nutrition (PN) solutions is still a concern, primarily in neonates [599]. The main sources of aluminum in PN solutions are calcium gluconate, phosphate salts, and acetate [600,601].…”
Section: Aluminummentioning
confidence: 99%
“…The main sources of aluminum in PN solutions are calcium gluconate, phosphate salts, and acetate [600,601]. The FDA established a safe upper limit for intravenous aluminum intake at 5 mg/kg/d [602]; however, multiple studies have shown that contamination of TPN products results in intakes of more than 5 mg/kg/d [597,599,603]. Prior to the FDA regulations TPN was associated with low levels of 1,25(OH) 2 D 3 [582], and patients developed a low-turnover osteomalacia with aluminum accumulation in bone [585].…”
Section: Aluminummentioning
confidence: 99%
“…Although aluminum-induced liver toxicity has been not reported in PN patients, animal studies have reported that aluminum in PN may induce portal infl ammation and liver injury by possibly blunting the bile canaliculi microvilli in a way similar to fi ndings in PNALD patients [ 49 , 50 ]. Although the Food and Drug Administration has mandated PN component product labeling for aluminum and recommended maximum daily exposure limits [ 48 ], aluminum contamination in PN remains problematic [ 51 ]. Therefore, periodic monitoring of serum aluminum is recommended especially in patients at risk for aluminum accumulation such as premature infants, PN-dependent patients, and those with decreased renal function.…”
Section: Manganese Copper and Aluminummentioning
confidence: 99%